Carbon stocks and sequestration potential of community forests in Bhutan - Sigyel Delma; Don Gilmour; Liz Sousa Ota; Katherine Warner; Karma Jigme Temphel; John Herbohn (Trees, Forests and People, 2024)
Community Forestry (CF) is recognized globally as a forest management regime with the potential to address deforestation and forest degradation, provide forest goods and services to local communities and contribute to climate change mitigation. Around 4% of Bhutan's forests are currently under CF management and these forests provide essential goods and services for local communities. However, the potential of CF in Bhutan to contribute to climate change mitigation is not well understood and has not been researched.In this study, we estimated the carbon stock and carbon sequestration of community forests in Bhutan by using data from the 2015 National Forest Inventory (NFI). The total biomass carbon in community forests was 130.3 Mg ha−1 (107.3–153.2) and the soil organic carbon was 52.8 Mg ha−1 (30.4–75.1). Carbon sequestration was 0.7 Mg ha−1 yr⁻¹. Other attributes: basal area, stem density and tree height, were also determined to assess forest condition and the potential to increase carbon sequestration.The values for biomass carbon in Bhutan's community forests as well as the non-community forests (all other forests) were similar to those reported from Forest Resource Assessment and NFI for forests in Nepal and the Indian Himalayan states respectively. Disaggregation of data from 38 research studies across the Himalayan region indicated that biomass carbon in Bhutan's forests was significantly lower than that in well-stocked (non-degraded) forests in the Indian and Nepal Himalayas. It was also much lower than that in Bhutan's Forest Management Units, which were used as an indicator of the potential upper limit of biomass carbon in Bhutan's forest environment. Similarly, basal area, stem density and mean tree height were also lower in Bhutan's community forests than in well-stocked forests in other Himalayan countries.The Bhutan Government is currently exploring the potential to generate revenue from the sale of carbon sequestered in its forests. This study confirms that there is potential to increase carbon sequestration by improving management of existing forests. Currently, the 107,866 ha of community forests in Bhutan store about 19 million Mg of carbon. With improved management by Community Forest Management Groups, which have the institutional capacity to control local management outcomes, the carbon stock could likely be doubled (to 40 million Mg of carbon), thereby demonstrating the potential of Community Forestry to play an important role in climate change mitigation, while not jeopardizing the provision of day-to-day goods and services to local communities.